2011
DOI: 10.1038/nsmb.2143
|View full text |Cite
|
Sign up to set email alerts
|

Total RNA sequencing reveals nascent transcription and widespread co-transcriptional splicing in the human brain

Abstract: Transcriptome sequencing allows for analysis of mature RNAs at base pair resolution. Here we show that RNA-seq can also be used for studying nascent RNAs undergoing transcription. We sequenced total RNA from human brain and liver and found a large fraction of reads (up to 40%) within introns. Intronic RNAs were abundant in brain tissue, particularly for genes involved in axonal growth and synaptic transmission. Moreover, we detected significant differences in intronic RNA levels between fetal and adult brains.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
290
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(325 citation statements)
references
References 49 publications
34
290
1
Order By: Relevance
“…Three recent studies based on RNA-seq provided evidence that intronic reads might correlate with transcriptional activity. In two of these, the read coverage along introns was related to nascent transcription in combination with co-transcriptional splicing events 24 and later was used to fit a detailed transcriptional model within a single sample 25 . More recently, levels of exonic reads were found to lag 15 min behind levels of intronic reads for a set of oscillating transcripts during Caenorhabditis elegans development, suggesting that intronic levels are a proxy for nascent transcription 26 .…”
mentioning
confidence: 99%
“…Three recent studies based on RNA-seq provided evidence that intronic reads might correlate with transcriptional activity. In two of these, the read coverage along introns was related to nascent transcription in combination with co-transcriptional splicing events 24 and later was used to fit a detailed transcriptional model within a single sample 25 . More recently, levels of exonic reads were found to lag 15 min behind levels of intronic reads for a set of oscillating transcripts during Caenorhabditis elegans development, suggesting that intronic levels are a proxy for nascent transcription 26 .…”
mentioning
confidence: 99%
“…First we examined the raw RNA read data for sequences that could be assembled to the intergenic spacer sequences, reasoning that polycistronic transcripts should produce intergenic regions and coding sequences in initially equal amounts. We anticipated these noncoding sequences, like introns, might be easily detectable, as intron sequences accumulate to roughly 1% of sequence reads in fission yeast (28) and are even more abundant in mammals (29). Because currently there are no known introns in Lingulodinium, we instead used read counts corresponding to the ITS, a spacer region excised during formation of mature rRNA, and found that the read ratio of ITS to mature rRNA is much higher than that of TAG spacer to mature ORF (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Another parameter for detecting de novo synthesized transcripts is the presence of intronic sequences due to incomplete cotranscriptional splicing (11). As shown in Fig.…”
Section: Gene Activation As Detected By the Appearance Of Incompletelymentioning
confidence: 99%